**Let D = {-5, -3, -1, 1, 3, 5}. Write the following statements using only negations, conjunctions and disjunctions: a) βπ₯π(π₯) b) βπ₯π(π₯) c) βπ₯((π₯ β 1) β π(π₯)) d) βπ₯((π₯ β₯ 0) β§ π(π₯)) e) βπ₯(οΏ’π(π₯)) β§ βπ₯((π₯ < 0) β π(π₯))**

The **Answer to the Question**

is below this banner.

**Here's the Solution to this Question**

a)Β $βxP(x)=P(-5)\lor P(-3)\lor P(-1)\lor P(1)\lor P(3)\lor P(5)$

b)Β $βxP(x)=P(-5)\land P(-3)\land P(-1)\land P(1)\land P(3)\land P(5)$

c)

$βπ₯((π₯ β 1) β π(π₯))=βπ₯(\neg(x\neq 1)\lor P(x))=(x=1)\lor P(1)$

d)

$βπ₯((π₯ β₯ 0) β§ π(π₯))=((x=1)\land P(1))\lor ((x=)\land P(3))\lor ((x=5)\land P(5))$

e)

$βπ₯(οΏ’π(π₯)) β§ βπ₯((π₯ < 0) β π(π₯)) =βπ₯(οΏ’π(π₯)) β§ βπ₯(\neg(π₯ < 0) \lor π(π₯))=$

$=βπ₯(οΏ’π(π₯)) β§ βπ₯((π₯ > 0) \lor π(π₯))=$

$=βπ₯(οΏ’π(π₯)) β§ (((π₯ =1) \lor π(1))\land ((π₯ =3) \lor π(3))\land ((π₯ =5) \lor π(5)))=$

$=(οΏ’π(-5)) β§ (((π₯ =1) \lor π(1))\land ((π₯ =3) \lor π(3))\land ((π₯ =5) \lor π(5)))\lor$

$\lor (οΏ’π(-3)) β§ (((π₯ =1) \lor π(π₯))\land ((π₯ =3) \lor π(3))\land ((π₯ =5) \lor π(5)))\lor$

$\lor (οΏ’π(-1)) β§ (((π₯ =1) \lor π(π₯))\land ((π₯ =3) \lor π(3))\land ((π₯ =5) \lor π(5)))\lor$

$\lor (οΏ’π(1)) β§ (((π₯ =1) \lor π(π₯))\land ((π₯ =3) \lor π(3))\land ((π₯ =5) \lor π(5)))\lor$

$\lor (οΏ’π(3)) β§ (((π₯ =1) \lor π(π₯))\land ((π₯ =3) \lor π(3))\land ((π₯ =5) \lor π(5)))\lor$

$\lor (οΏ’π(5)) β§ (((π₯ =1) \lor π(π₯))\land ((π₯ =3) \lor π(3))\land ((π₯ =5) \lor π(5)))$